Rapid determination and continuous monitoring of propofol in microliter whole blood sample during anesthesia by paper spray ionization-mass spectrometry - Liu, Ying; Zhang, Xiao-Hui; Mi, Wei-Dong; Zhou, Ying-Lin; Zhang, Chang-Sheng; Zhang, Xin-Xiang (Analytical and bioanalytical chemistry, 2021)
Propofol is a widely used intravenous anesthetic agent in sedation and general anesthesia. To improve the safety and maintain the depth of anesthesia, it is important to develop a rapid, sensitive, and reliable method to monitor the concentration of propofol in blood during anesthesia continuously. Here, we present a novel strategy based on paper spray ionization-mass spectrometry (PSI-MS) to detect propofol. Samples (in 10 μL) were mixed with methanol as protein precipitation solvent and 2,6-dimethylphenol as internal standard. Protein micro-precipitation was achieved with methanol by vortexing and centrifuging for 5 s each, and propofol was extracted to the supernatant. PSI-MS was performed in negative ionization mode, and MS signal lasted for 1 min. The analysis of a single sample was completed within 2 min. The area ratios of propofol to internal standard were calculated for quantification. Limit of detection of 5.5 ng mL −1 and limit of quantification of 18.2 ng mL −1 were achieved for propofol in whole blood. Calibration curve was linear in the range of 0.02–10 μg mL −1 . The developed method was used successfully in monitoring the propofol concentration in 3 patients’ whole blood during anesthesia, showing its further application in controlling and feeding-back target concentration infusion. Graphical abstract